Gauging the effects of fiscal stimulus packages in the euro area - Günter Coenen; Roland Straub; Mathias Trabandt (European Central Bank (ECB), 2012)
We seek to quantify the impact on euro area GDP of the European Economic Recovery Plan (EERP) enacted in response to the financial crisis of 2008-09. To do so, we estimate an extended version of the ECB's New Area-Wide Model with a richly specified fiscal sector. The estimation results point to the existence of important complementarities between private and government consumption and, to a lesser extent, between private and public capital. We first examine the implied present-value multipliers for seven distinct fiscal instruments and show that the estimated complementarities result in fiscal multipliers larger than one for government consumption and investment. We highlight the importance of monetary accommodation for these findings. We then show that the EERP, if implemented as initially enacted, had a sizeable, although short-lived impact on euro area GDP. Since the EERP comprised both revenue and expenditurebased fiscal stimulus measures, the total multiplier is below unity.
Keywords: C11; E32; E62; 330; Bayesian inference; DSGE modelling; euro area; European Economic Recovery Plan; fiscal multiplier; Fiscal Policy; Antizyklische Finanzpolitik; Konjunktur; Multiplikator; DSGE-Modell; Bayes-Statistik; Eurozone; EU-Staaten